EFFECT OF NANO SILVER (AG NP-124) AS EGG SHELL SANITIZER ON THE KEEPING QUALITY OF TABLE EGGS - C. Pandian; R. Richard Churchil; S. Manoharan; P.Veeramani (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Nano silver particles are valuable alternative for antibiotics and disinfectants as it is relatively free of adverse effects. Nano silver particles (AgNPs) have new physical and chemical characteristics enabling it to have a strong antibacterial activity and used today more as a high disinfectant in poultry farms. This study was aimed to evaluate the effect of different concentrations of 10, 20 and 50 ppm of Ag-NPs as egg shell sanitizer and assess the microbial count on the egg shell surface during different storage conditions. The total bacterial count on the egg shell and egg quality characteristics were carried out on 1, 7, 14, 21 and 28 days of storage after sanitation. Presence of nano silver and distribution on egg shell surface were determined using transmission electron microscopy. Results showed that bacterial loads on the egg shell were declined with the increased concentration of Ag-NPs used and the 50 ppm concentration of Ag-NPs had 1-3 log reduction in the total bacterial count on one day after disinfection in the egg shell surface which were comparable with the positive control (1% Kohrsolin) used in the trial. However, the external and internal qualities of eggs did not show any significance difference among different treatments during different storage days. However, nano silver 50 ppm had comparatively better zone of inhibition than 10 and 20 ppm levels in disc diffusion method. This study concluded that using Ag-NPs at 50 ppm concentration in disinfecting chicken egg can effectively reduce bacterial load on egg shell.